Optimistic minimax search for noncooperative switched control with or without dwell time. (February 2020) - Buşoniu, Lucian; Rejeb, Jihene Ben; Lal, Ioana; Morărescu, Irinel-Constantin; Daafouz, Jamal
Abstract: We consider adversarial problems in which two agents control two switching signals, the first agent aiming to maximize a discounted sum of rewards, and the second aiming to minimize it. Both signals may be subject to constraints on the dwell time after a switch. We search the tree of possible mode sequences with an algorithm called optimistic minimax search with dwell time (OMSd), showing that it obtains a solution close to the minimax-optimal one, and we characterize the rate at which the suboptimality goes to zero. The analysis is driven by a novel measure of problem complexity, and it is first given in the general dwell-time case, after which it is specialized to the unconstrained case. We exemplify the framework for networked control systems where the minimizer signal is a discrete time delay on the control channel, and we provide extensive simulations and a real-time experiment for nonlinear systems of this type.